2022
DOI: 10.1111/hae.14628
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the pedHALshort and HALshort in Dutch children and adults with haemophilia

Abstract: Introduction The Haemophilia Activities List (HAL) and paediatric HAL assess self‐reported limitations in various daily activities. To reduce patient burden, shorter versions of the pedHAL (22 items) and HAL (18 items) have been developed. Aim This study aimed to determine the agreement between the pedHAL/HALfull and pedHAL/HALshort and construct validity and internal consistency of the pedHAL/HALshort in persons with haemophilia (PWH). Methods A cross‐sectional secondary analysis of the Hemophilia in the Neth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
2
2
0
Order By: Relevance
“…The internal consistency of the PedHALshort questionnaire in the total group was high, with Cronbach's α value of 0.85 (0.74–0.92). These results are in accordance with research in the Netherlands which obtained Cronbach's α value of 0.95–0.97 12 . The lowest ICC in the age group of 4−7 years may be attributed to the smaller group size and the fact that parents completed the form.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The internal consistency of the PedHALshort questionnaire in the total group was high, with Cronbach's α value of 0.85 (0.74–0.92). These results are in accordance with research in the Netherlands which obtained Cronbach's α value of 0.95–0.97 12 . The lowest ICC in the age group of 4−7 years may be attributed to the smaller group size and the fact that parents completed the form.…”
Section: Discussionsupporting
confidence: 91%
“…These findings align with the construct validity tested in the Netherlands where it was linked to the Haemophilia & Exercise Project–Test–Questionnaire (HEP‐test‐Q) with the results of PedHALshort ( r = .42) and CHO‐KLAT (PedHALshort r = .44) showing a moderate correlation 12 . Research of physical function in adolescents with haemophilia in the UK also found a moderate correlation between PedHAL and Haemo‐QoL SF r = −.561 ( p < .0001) 13 .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The normalised HAL/PedHAL score was categorised as ≥90 (good mobility and physical activities), 65−90 (fair), < 65 (poor). The cut‐offs for both tools were defined on clinical experience and published study on BPI 35–36 and HAL/PedHAL 37–39 performance, respectively. A categorisation scheme is reported in Table S3 and combination of three levels of these three items to form possible health states in Figure S2.…”
Section: Resultsmentioning
confidence: 99%